PENGGUNAAN AKTIVATOR STARDEC TERHADAP KUALITAS KOMPOS BERBAHAN DASAR PELEPAH SAWIT DAN FESES SAPI - alfarezy, muhammad alfarezy; syafria, Hardi syafria; Adriani, Adriani (Jurnal Peternakan Nusantara, 2022)
The aim of this study was to determine the effect of the addition of Stardec activator on the quality of the compost using palm fronds and cow feces as the basic ingredients. This research was carried out for ±1 month of composting in the laboratory for livestock and forage cultivation, Faculty of Animal Husbandry, Jambi University and Soil Science Laboratory, Faculty of Agriculture, UNAND. This research was carried out using a completely randomized design (CRD) consisting of 4 treatments and 5 replications. The materials used were palm fronds 70% + sai feces 25% + urea 1% + bran 4%, with the use of stardek A0 0%, A1 0.5%, A2 1% and A3 1.5%. The observed variables were pH, and the elements contained therein (carbon, nitrogen, phosphorus, potassium, and the C/N ratio). from research that has been done shows pH (6-7). The results of statistical analysis showed that the addition of Stardec had a very significant effect (P<0.01) on carbon, phosphorus and potassium. No significant effect (P>0.05) on nitrogen and C/N ratio. Based on the results of the study, the best results were obtained from the content contained in the compost such as (C,N,P,K and C/N ratio) and pH, namely the addition of 1.5% Stardec.